The Effect Of Sustainable Professional Development On The Competence And Performance Of Elementary School Teachers In Learning Innovation - Nurmalina Nurmalina; Suhartono Suhartono (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2021)
The research aims to describe the effect of Continuing Professional Development (PKB) on the competence and performance of elementary school teachers in learning innovation, and analyze how much influence PKB has on the competence and performance of elementary school teachers in carrying out learning innovations. Quantitative research method with simple random sampling technique. The population is 116 people and the sample used is 90 respondents. The resulting instruments include: PKB planning, self-development, scientific publications and innovative works with indicators following and implementing training, workshops, seminars, making innovative works and scientific publications in teacher performance. While learning innovation is measured through learning programs, classroom management, mastery of teaching materials, use of methods, media and evaluation of learning. The application of reflective actions and the results of Classroom Action Research reports on a regular basis become a benchmark for more professional teacher performance. Statistical data shows that: 1) there is a positive and significant effect of the PKB variable on teacher competence by 9.28%, 2) there is a positive and significant effect of the PKB variable on teacher performance by 4.84% and 3) there is a positive and significant influence on teacher performance. Simultaneous PKB variable on teacher competence and performance is 14.12%. Continuing Professional Development has a significant influence on teacher competence and performance which can be designed, tested and measured by the relevant agencies and has a broad impact on the innovative culture of teacher learning during the pandemic.